CAUSES OF PERINATAL MORTALITY IN BUKHARA (Conferencea, 2022)
The causes of perinatal death in the territory of the Bukhara region have been studied. Perinatal mortality is one of the most important indicators that most fully characterize the social well-being of society, and therefore, along with others, it is most justifiably in the center of attention when assessing population processes.